Syndactylism of Fingers: A Clinical Study - Dipak Kumar Ghosh; Murari Mohan Mukherjee (Indian Journal of Plastic Surgery)
Different aspects of 44 cases of Syndaetylism secen and treated at Department of Plastic Surgery, S. S. K. M. Hospital and IPGMER 1958 and 1966, followed up for varying periods from 1 to 8 years are described. The probable aetiological factors, the clinical variations, and the treatment are discussed.